Development and application of maintenance decision-making support system for aircraft fleet. (December 2017) - Lin, Lin; Luo, Bin; Zhong, ShiSheng
Highlights: A new reliability evaluation method based on the real-time load information for aircraft structures. Minimize the maintenance cost and maximize the availability of a fleet. A multi-objective decision-making model based on condition-based-maintenance. A maintenance decision-making support system for integrating the process of data acquisition, data processing and maintenance decision-making. Abstract: With the arrival of on-board monitoring systems for aircraft structures, maintainers have access to a near real-time assessment of component health. Due to the traditional reliability assessment methods for aircraft structures lack of the ability to make full use of real-time status information collected by the monitoring systems, a new reliability evaluation method based on the real-time load information is proposed for aircraft structural reliability. Condition-based-maintenance is a maintenance scheme which recommends maintenance decisions according to equipment status collected by monitoring systems over a period of time. As most researches on condition-based maintenance for aircraft focused on solely minimizing maintenance cost or maximizing the availability of single aircraft, a multi-objective decision-making model based on condition-based-maintenance concentrated on both minimizing the maintenance cost and maximizing the availability of a fleet (total number of available aircraft in fleet) is established for an aircraft fleet. Finally, a maintenance decision-making support system (MDMSS) is developed based on the proposed model. The system integrates the process of data acquisition (real-time status information of aircraft), data processing (reliability assessment of aircraft structures) as well as maintenance decision-making. Therefore, it simplifies the complex process of equipment management and takes a step further in engineering application.